2021
DOI: 10.1021/acs.nanolett.1c03089
|View full text |Cite
|
Sign up to set email alerts
|

GSH-Responsive Nanoprodrug to Inhibit Glycolysis and Alleviate Immunosuppression for Cancer Therapy

Abstract: Blocking energy metabolism of cancer cells and simultaneously stimulating the immune system to perform immune attack are significant for cancer treatment. However, how to potently deliver different drugs with these functions remains a challenge. Herein, we synthesized a nanoprodrug formed by a F127-coated drug dimer to inhibit glycolysis of cancer cells and alleviate the immunosuppressive microenvironment. The dimer was delicately constructed to connect lonidamine (LND) and NLG919 by a disulfide bond which can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 41 publications
1
68
0
Order By: Relevance
“…On the other hand, as the end product of glycolysis, lactate also can be regarded as another indicator for verifying whether glycolysis inhibition. Specifically, the glycolysis inhibition is typically accompanied with the reduction in lactate 10 . The result in Figure 4 E demonstrated that as compared with the free drugs, the LND-Pep-cyclen was more effective in decreasing the intracellular lactate concentration, which was coincident with the result in Figure 4 C. It is well known that the first step in glycolysis is the glucose being catalyzed by HK to 6-phosphate glucose.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, as the end product of glycolysis, lactate also can be regarded as another indicator for verifying whether glycolysis inhibition. Specifically, the glycolysis inhibition is typically accompanied with the reduction in lactate 10 . The result in Figure 4 E demonstrated that as compared with the free drugs, the LND-Pep-cyclen was more effective in decreasing the intracellular lactate concentration, which was coincident with the result in Figure 4 C. It is well known that the first step in glycolysis is the glucose being catalyzed by HK to 6-phosphate glucose.…”
Section: Resultsmentioning
confidence: 99%
“…As an effective inhibitor of glycolysis, Lonidamine (LND) is an effective inhibitor of hexokinase II (HK II), a rate-limiting enzyme for glycolysis pathways. A GSH-responsive nanodrug that is loaded with LND restrains the glycolysis of tumor cells and inhibits tumor growth (Liu et al, 2021). In a similar manner, a nanodrug consists of 1-(4-pyridyl)-3-(2-quinoline)-2-propyl-1-one (PFK15), which is a PFKFB3 inhibitor targeting glycolysis metabolism (Zhao et al, 2020a).…”
Section: Aerobic Glycolysis and Mitochondrial Aerobic Respirationmentioning
confidence: 99%
“…Several researchers have focused on developing functional carriers with reduction responsiveness based on two strategies: insertion of disulfide bonds in the polymer backbone or using reduction-sensitive cross-linking molecules ( Gulfam et al, 2017 ; Conte et al, 2018 ; Deng et al, 2018 ; Monteiro et al, 2020 ). Glutathione (GSH) levels inside and outside cancer cells are markedly different ( Lai et al, 2021 ; Liu et al, 2021 ). Nanocarriers with reducing properties can achieve drug release more accurately and rapidly.…”
Section: Non-specific Targeted Therapeutic Nanocarriers For Treatment Of Bladder Cancermentioning
confidence: 99%